Estudo do desempenho do processo de retificação eletroquímica na usinagem do aço rápido ABNT M6 - Ramos, Carlos Alberto Domingos (1999)
An important and significant advantage of the electrochemical grinding process (ECG) over conventional grinding machining of hard-to-machined and high-strength materiais, are the increase of material removal rate and better surface characteristics without changing mechanical properties of the material. To analyse these effects, high-speed Steel ABNT M6 was machined by ECG process using tangential plunging grinding operation with stable table. The machine used was derived from a conventional grinding machine. It was used CBN grinding wheel. The performance of the operation was studied and the results compared with the conventional grinding process. This work also analysed the effects of some process variables, such as the electrolyte flow rate, the current density and the applied load on the supply source, upon surface roughness, nose radius and hardness of the machined surface. The findings indicated that the electrochemical-abrasive process was effective and show a tendency in decreasing surface roughness with the increase of metal removal rate.